EFEKTIVITAS PERAN GURU PAI DALAM PENDAMPINGAN PENGUASAAN MATERI AGAMA ISLAM BAGI ANAK BERKEBUTUHAN KHUSUS - Husen, Fadlil Khusaini Ali (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2024)
This study aims to describe and analyze the effectiveness of assistance in mastering Islamic Religious Education (PAI) learning materials for students with special needs at SMP Qaryah Thayyibah Kedungbanteng and SMPIT Harapan Bunda Purwokerto. This research is motivated by the increasing number of students with special needs in inclusive public schools and the importance of assistance in helping them understand religious materials and practices according to their abilities and needs. This study employs a qualitative approach with a comparative study design. Data were collected through in-depth interviews, observations, and documentation. The research subjects included school principals, Islamic Religious Education teachers, Special Education Teachers (Special Assistant Teachers/GPK), and other related parties. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results of the study indicate that assistance in mastering Islamic Religious Education materials for students with special needs in both schools has been implemented quite effectively, although with different characteristics. SMPIT Harapan Bunda Purwokerto, which is supported by the presence of Special Assistant Teachers (GPK), demonstrates more structured, intensive, and directed assistance in learning activities, religious practices, and evaluation of students’ development. Meanwhile, SMP Qaryah Thayyibah Kedungbanteng, despite not having Special Assistant Teachers, is still able to implement effective assistance through individualized approaches, humanistic learning methods, and the use of direct practice in Islamic Religious Education learning. The implications of this study show that the presence of Special Assistant Teachers plays a significant role in optimizing assistance for mastering Islamic Religious Education materials for students with special needs. Therefore, strengthening inclusive education policies, improving the competence of Islamic Religious Education teachers, and enhancing collaboration among schools, teachers, and parents are necessary to create inclusive and student-friendly Islamic Religious Education learning for students with special needs.